Detection of Signal Regulatory Protein α in Saimiri sciureus (Squirrel Monkey) by Anti-Human Monoclonal Antibody - Souza, Hugo Amorim dos Santos de; Costa-Correa, Edmar Henrique; Bianco-Junior, Cesare; Andrade, Márcia Cristina Ribeiro; Lima-Junior, Josué da Costa; Pratt-Riccio, Lilian Rose; Daniel-Ribeiro, Cláudio Tadeu; Totino, Paulo Renato Rivas (Frontiers in Immunology, 2017)
Non-human primates (NHP) are suitable models for studying different aspects of the human system, including pathogenesis and protective immunity to many diseases. However, the lack of specific immunological reagents for neo-tropical monkeys, such as Saimiri sciureus, is still a major factor limiting studies in these models. An alternative strategy to circumvent this obstacle has been the selection of immunological reagents directed to humans, which present cross-reactivity with NHP molecules. In this context and considering the key role of inhibitory immunoreceptors - such as the signal regulatory protein α (SIRPα) - in the regulation of immune responses, in the present study we attempted to evaluate the ability of anti-human SIRPα monoclonal antibodies to recognize SIRPα in antigen-presenting S. sciureus peripheral blood mononuclear cells (PBMC). As shown by flow cytometry analysis, the profile of anti-SIRPα staining as well as the levels of SIRPα-positive cells in PBMC from S. sciureus were similar to those observed in human PBMC. Furthermore, using anti-SIRPα monoclonal antibody, it was possible to detect a decrease of the SIRPα levels on surface of S. sciureus cells after in vitro stimulation with lipopolysaccharides. Lastly, using computed-based analysis we observed a high degree of conservation of SIRPα across six species of primates and the presence of shared epitopes in the extracellular domain between humans and Saimiri genus that could be targeted by antibodies. In conclusion, we have identified a commercially available anti-human monoclonal antibody that is able to detect SIRPα of S. sciureus monkeys and that, therefore, can facilitate the study of the immunomodulatory role of SIRPα when S. sciureus is used as a model.